Benefits and challenges of an omnichannel retail strategy for luxury fashion brands - Salsano, Alessandro (2020)
Luxury is neither a product, an object, a service nor a concept or a lifestyle. It is an identity, a philosophy and a culture. As a business sector and management discipline, these characteristics signify the presence of challenges in the integration of luxury branding within the Internet and digital environment and the requirement of intricate strategies to overcome them (Okonkwo, 2010). The digital transformation that the world has seenin the lastdecades has been capable ofreshaping the way every business is organized. While most of the retail businessesdid not face many difficulties when going throughdigitalization, the Luxury Fashion industry did .Luxury Fashion system today faces the challenge of renewing business models to intercept what is changing in the retail environment and in the consumer base. One way to do so is to implement a successful Omnichannel Strategy. The present workaims to present the benefitsand challengeslinked to the implementation of the strategy, from a managerial point of view. The results will be achievedby leveraging qualitative research conducted with professionals ofthe industry and the available literature.